THE EFFECTIVENESS OF IMAGINATION GUIDANCE ON REDUCING HOSPITALIZATION STRESS IN SCHOOL-AGE CHILDREN 7-12 YEARS - Niar; Fransiska Firna (Universitas Islam Negeri Alauddin Makassar, 2023)
Hospitality stress is an unpleasant experience due to the incompatibility of individual conditions with the environment accompanied by changes in behavior. The purpose of this study was to determine the effect of imagination effectivitas on reducing stress hospitalization for school children aged 7-12 years in the Asoka Treatment Room in Polewali Mandar Hospital. Imagery guidance is a technique that can be used at home and can help to relax and get rid of the burden of thoughts or stress that is being experienced. This research is an experimental research with research design is a quasy experiment with pre and post test design. The sampling technique used in this study was Accidental Sampling with 22 respondents as the research subjects. In this study data collection using observation sheets. Data analysis used the McNemar test to see the effect on a measurement measurement with a significance level of Î± = 0.05. Data processing results were carried out using data analysis with McNemar test which showed that there was an effect of Imagination Guidance on Decreasing Stress Hospitalization with a significant level of p = 0,000